Revitalizing the Observatorio Naval de Buenos Aires (ONBA): Modernization, outreach, and new challenges - Miculán, Romina Gisele (2025)
The Observatorio Naval de Buenos Aires (ONBA) is undergoing a compre hensive modernization to strengthen its role as a public service institution, aligned with the mission of national defense, scientific development, time dis semination, and calibration. ONBA has upgraded its Time and Frequency Laboratory, ensuring the accuracy of Argentina’s official time [1] and con tributing to the Bureau International des Poids et Mesures (BIPM). Since 1934, ONBA has maintained the uninterrupted publication of the Almanaque Náutico, providing precise astronomical and navigational data. Additionally, it continues to offer expertise in judicial inquiries requiring astronomical analysis.